Left ventricular hypertrophy in experimental chronic kidney disease is associated with reduced expression of cardiac Kruppel-like factor 15 - Sheila K. Patel (BMC Nephrology, 2018)
Abstract Background Left ventricular hypertrophy (LVH) increases the risk of death in chronic kidney disease (CKD). The transcription factor Kruppel-like factor 15 (KLF15) is expressed in the heart and regulates cardiac remodelling through inhibition of hypertrophy and fibrosis. It is unknown if KLF15 expression is changed in CKD induced LVH, or whether expression is modulated by blood pressure reduction using angiotensin converting enzyme (ACE) inhibition. Methods CKD was induced in Sprague–Dawley rats by subtotal nephrectomy (STNx), and rats received vehicle (n = 10) or ACE inhibition (ramipril, 1 mg/kg/day, n = 10) for 4 weeks. Control, sham-operated rats (n = 9) received vehicle. Cardiac structure and function and expression of KLF15 were assessed. Results STNx caused impaired kidney function (P < 0.001), hypertension (P < 0.01), LVH (P < 0.001) and fibrosis (P < 0.05). LVH was associated with increased gene expression of hypertrophic markers, atrial natriuretic peptide (ANP), brain natriuretic peptide (BNP, P < 0.01) and connective tissue growth factor (CTGF) (P < 0.05). Cardiac KLF15 mRNA and protein expression were reduced (P < 0.05) in STNx and levels of the transcription regulator, GATA binding protein 4 were increased (P < 0.05). Ramipril reduced blood pressure (P < 0.001), LVH (P < 0.001) and fibrosis (P < 0.05), and increased cardiac KLF15 gene (P < 0.05) and protein levels (P < 0.01). This was associated with reduced ANP, BNP and CTGF mRNA (all P < 0.05). Conclusion This is the first evidence that loss of cardiac KLF15 in CKD induced LVH is associated with unchecked trophic and fibrotic signalling, and that ACE inhibition ameliorates loss of cardiac KLF15.